2023
DOI: 10.3390/bs13100810
|View full text |Cite
|
Sign up to set email alerts
|

Does the Effect of Stress on Smartphone Addiction Vary Depending on the Gender and Type of Addiction?

Wei Tu,
Yangang Nie,
Qingqi Liu

Abstract: Stress is closely associated with smartphone addiction. Nevertheless, there is a dearth of studies investigating the potential variation in the effect of stress on smartphone addiction based on the specific addiction type and gender. We conducted a cross-sectional questionnaire survey among 596 high school students. The results revealed that the effect size of stress on smartphone addiction varied across different types of addiction. The strongest relationship was observed between stress and social media addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Two items assess the inability to control cravings, two items gauge anxiety and feeling lost, one item evaluates withdrawal and escape, and one item examines productivity loss. Previous research conducted among Chinese adolescents Tu et al, 2023) has demonstrated that this subscale exhibits high levels of reliability and validity. Cronbach's α for this measure was .86.…”
Section: Measurements Gaming Disordermentioning
confidence: 96%
“…Two items assess the inability to control cravings, two items gauge anxiety and feeling lost, one item evaluates withdrawal and escape, and one item examines productivity loss. Previous research conducted among Chinese adolescents Tu et al, 2023) has demonstrated that this subscale exhibits high levels of reliability and validity. Cronbach's α for this measure was .86.…”
Section: Measurements Gaming Disordermentioning
confidence: 96%